Niezwykłe istoty w Księdze Jana Mandeville’a .......... 161 - Krawiec, Adam (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
UNUSUAL CREATURES IN THE BOOK OF JOHN MANDEVILLEThe aim of the article is to present the issues related to the descriptions of extraordinary creatures in The Book of John Mandeville – a description of the eastern part of the known world created in the mid-14th century in the form of a fictional travelogue. This is a topic that is relatively rarely present in the previous literature on the subject concerning this work, which enjoyed great popularity in the 14th–16th centuries, and which functioned not only in the author’s version, but also in many alternative versions, differing in language and content. The article characterizes respective categories of extraordinary creatures described by the author of the studied text, with particular emphasis on monstrous peoples and animals. Differences in this respect in selected versions of The Book of John Mandeville are indicated. An attempt is made to systematically classify the extraordinary animals described in the work from the point of view of the elements based on which the author decided to consider them extraordinary. The topic of extraordinary creatures is placed in the broader context of the author’s vision of the world. An attempt was also made to answer the question about the role played by descriptions of various unusual facts, creatures, customs and objects in the structure of the work.